Phenotyping low phosphate responses of Eutrema salsugineum ecotypes and their recombinant inbred lines - Li, Laura (My University, 2025)
Phosphorus, an essential nutrient for plants, is provided to crops in the form of phosphate containing fertilizers to maximize yield. Accessible rock phosphate deposits used in producing fertilizers are dwindling while harmful environmental impacts of increased fertilizer use and production grow, making it imperative to reduce our reliance on this nutrient. We study two ecotypes of Eutrema salsugineum, an extremophile crucifer related to the oilseed crop canola. The ecotype from Yukon, Canada, is tolerant to many abiotic stressors including low-phosphate while the ecotype from Shandong, China, is sensitive to low-phosphate. In this study we used 11 recombinant inbred lines (RILs) produced by crossing the two ecotypes to screen for their low-phosphate sensitivity. Seedlings were grown on agar with low (0 or 0.05 mM) or high (0.5 mM) phosphate and plants were grown up to 11 weeks in pots of soil-less media and fertilized with solutions lacking or supplemented with phosphate (0 or 2.5 mM). Seedling root architectural traits and root/shoot biomass were measured and plants in pots were analyzed by monitoring fluorescence parameters, leaf coverage and shoot biomass. Expression of Induced by Phosphate Starvation2 (IPS2) and five ecotype-specific genes were assessed for their utility as treatment and/or genotypic markers. Among root traits, primary root length was a reliable screening trait for identifying low-phosphate tolerant RILs while lateral root length or density gave inconsistent assignments. Non-photochemical quenching data suggests improved capacities to dissipate excess energy in phosphate-deprived plants, particularly Yukon plants, but further testing is needed given this unanticipated finding. IPS2 expression was a reliable bioindicator of low-phosphate exposure while the ecotype-specific genes proved too small a testing group to reveal meaningful patterns. Genome and transcriptome sequencing combined with a focused phenotype screen like primary root length offer a plausible path to identify genes underlying low-phosphate tolerance in plants.